The influence of ethical leadership and climate towards intention - Nurul Khair, Ishak; Yuserrie, Zainuddin; Hasnah, Haron (GBMR, 2022)
Purpose: Unethical behavior is also a university issue. This kind of behavior can affect academicians, administrators, or students. The elements of ethical leadership and ethical climate that may impact a person’s decision to engage in such action are identified. Therefore, this study aims to find out whether those factors can cause academicians to behave unethically. Methodology: A quantitative survey method was adopted to gather response from 100 lecturers. The data were analyzed using the partial least squares structural equation modeling (PLS-SEM) technique and Smart PLS 3 software. Findings: The findings of the study found that ethical climate had a positive and significant relationship with intention while there is a negative relationship between ethical leadership and intention. Practical implications: This study helps to understand the importance and role of ethical leadership and ethical climate in higher learning institutions, managing situations involving ethical decisions, thus improving the functions of the organizations.